Cultural Performances and Practices in Kirtipur: A Mythic Perspective on Lakhe Dance, Arts and Literature of Newars - Gautam, Mani Bhadra (Cognition, 2022)
Kirtipur is a historical place of Nepal that is important for its geographical location, arts and cultural performances. Majority of the people living in Kirtipur are Newars and they perform special Newar Dance, Lakhe Dance, Satgaunle Jatra, Ghatemangal etc. The performances help to study the Newars arts, culture and literature which are quite interesting while studying from mythical perspective. Myth centers on transformation of consciousness, the hero journey, human feelings, understanding, observation, actions, experiences and, life and death rituals. This study undergoes on cultural performances and spiritual growth of the time derived themes and ideas from a long standing, scenarios/socio-historical context. Primitive mental images inherited from the earliest human ancestors are reflected in Lakhe Dance performances of Kirtipur as they perform in different forms. Objective of this study is to capture the mythical images and present events in field based method relating with human feelings and thoughts in social-survey for views collection. It also subjectivizes on human cruelty, socio-cultural violence and dis-harmony representing the past reality and present excitement for socio-cultural changes in a different way. This article presents a brief sketch of a new perspective on cultural orientation to mythical world as Lakhe Dance reflects practices of the past and creates the meanings to the present. Lakhe Dance is one of the tools to excavate Kirtipur’s history through Cultural Studies in this research that helps to carry out the expected result. I have tried to study and examine the performances and analyze the narratives in Newar literature from mythical perspectives.